Analisis Gaya Bahasa Dalam Lirik Lagu “Alexandra” Karya Hindia - Ridho Rahmatulloh; Arfian Suryasuciramadhan; Muhamad Sobahri; Muhamad Fauzan Kurniawan; Aldo Savero Zahran (Institut Nalanda, 2024)
Literature is a type of artwork that blends the beauty of language with the intent to convey an idea or message. Literature is very important for human life because it can influence human thinking and perspective. Song lyrics are one type of literary work that can move feelings in a beautiful and interesting way. One of the poets / songwriters of the country is the Indies. He is a solo singer with the real name